Analysis of Sustainable Ecotourism Development: Case Study - Darmawan, I Kadek Ari; Widnyana, I Ketut; Maba, Wayan; Vipriyanti, Nyoman Utari (Journal La Sociale, 2026)
Sustainable ecotourism development is an important strategy in regional development that integrates economic, social, and environmental aspects. Teba Majalangu, located in Kesiman Kertalangu Village, East Denpasar District, which means “a place to learn about nature,” has great potential to be developed as a sustainable ecotourism destination. This study aims to analyze the development of ecotourism in Teba Majalangu by identifying its potential, challenges, and appropriate development strategies. The research method employs both qualitative and quantitative approaches using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). Data were obtained through field observations, interviews with village officials, tourism managers, and local communities, as well as documentation studies. The results show that Teba Majalangu possesses strengths such as unique natural landscapes, local cultural values, and community support, but still faces weaknesses such as limited infrastructure, lack of promotion, and low human resource capacity. Development opportunities are supported by the growing awareness of ecotourism among tourists, government support, and potential collaboration with various stakeholders, while threats include competition from other tourist destinations, environmental degradation, and climate change. Recommended strategies include optimizing natural and cultural potential, improving infrastructure and human resource capacity, strengthening promotion, and innovating sustainable tourism products. Through a holistic approach involving communities, government, and related stakeholders, the development of Teba Majalangu ecotourism is expected to improve local welfare while preserving the environment and culture.